KERAGAMAN BUAH PALA (Myristica fragrans Houtt) DI KABUPATEN KEPULAUAN SANGIHE DAN KABUPATEN SITARO - ., Robert; Runtunuwu, S. D.; Rogi, J. E.X.; Pamandungan, Yefta (EUGENIA, 2015)
ABSTRACT Â  This study aims to determine the nutmeg crop diversity is based on the character of the fruit, seeds, nutmeg mace in Sangihe Island Regency (Island of Sangihe) and District SITARO (Siau Island). The method used is the method of direct observation at the farmer's planting area nutmeg. Location research based on secondary data, namely the districts and villages producer of nutmeg, then determined the three observation points in each study site. Each observation point is determined 10 samples to be observed fruit trees, and every tree observed 20 fruit ready for harvest. Samples of plants is determined by: 1) Age of plants, which is about 15-30 years, and 2) The state of the plant, which is being fruitful and healthy tree. Observations carried out on: 1) The shape of fruit, 2) Color rind 3) Thick flesh, 4) Weight pieces, 5) The length of the fruit, 6) diameter pieces, 7) The color of the fruit flesh, 8) Weight seed fresh, 9) Lengh seed, 10) diameter seed, 11) weightÂ  mace fresh, 12) Color mace. The results showed: 1) The shape of fruit and nutmeg seeds in Sangihe Islands Regency is more diverse than in the District Sitaro. 2) The highest weight of fresh nutmeg obtained from the location Talawid weighing 57.95 g fresh weight and r lowest nutmeg obtained from the location Karatung I is weighing 35.91 g fresh weight nutmeg while the highest was obtained from the location that is weighing 9.45 g Talawid and the lowest seed fresh weight was obtained from the location Karatung I are weighing 6.75g. 3) The same colors are red blood mace. Keywords: nutmeg plant, diversity of fruit, Sangihe, SITARO